DEKONSTRUKSI PERUBAHAN KARAKTER KEBENDAAN IMAJINASI KREATIF DALAM KARYA SENI LUKIS - Yudha, I Made Bendi; Gulendra, I Wayan (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2021)
Art is a reflection and sensitivity of spiritual experience related to environmental phenomena. It is the values of life which constantly offer anxiety over the changes. Exploration through observation and scrutiny on this phenomenon stimulates imaginative and expressive spirit. Therefore, it is necessary to do a deeper approach on life values through understanding and appreciation. This can be transformed into visual works which present moral messages of lifereality. Life today is full of a challenge that changes the mental attitude. There is a tendency of being materialistic which affects the uncontrolled behavior of life. So, crime is rampant with different motives and forms in society. Abuse of power, authority, law and religion are only a mask to meet the goal of temporary interests. Money and property have been embezzled the soul and the sense of human’s life. These phenomena have stimulated spiritual and emotional feeling to lift up an idea about the meaning of changes. The admirers of changes took pride of this material world. Life is a process of love, sorrow, sadness and starch as the nature of life. All material elements are not eternal. They are being bound by the limitation of the natural law of life cycle; the birth, growth and destruction (pralina). Appreciating these values can create ideas in understanding of the character of the material elements such as aging, decrepitude, distraction and destruction. In the creation process, this idea is very important.